Pore structure changes in free-standing single-wall carbon nanotube film on vacuum high-temperature annealing. (October 2022) - Kamijyou, Yuito; Kukobat, Radovan; Furuse, Ayumi; Otsuka, Hayato; Fujisawa, Kazunori; Hayashi, Takuya; Sakai, Toshio; Kaneko, Katsumi
Highlights: Highly pure and crystalline free-standing SWCNT films were fabricated. Impurities can be removed completely by vacuum high-temperature annealing. Vacuum annealing can improve crystallinity of SWCNT film. Vacuum annealing eliminates nanowindows and other defects from SWCNT film. Abstract: The fabrication of free-standing single-wall carbon nanotube (SWCNT) film is promising for better understanding of SWCNT and many applications. Here we fabricated highly pure and crystalline free-standing SWCNT film using vacuum high-temperature annealing. Impurities can be removed thoroughly by vacuum annealing at 2073 K and 10 −1 Pa for 3 h. Also, the vacuum annealing was quite efficient for removing nanowindows and improving crystallinity of the SWCNT film. The transmission electron microscopic observation and X-ray diffraction confirmed almost no change in the average tube diameter and bundle structure of SWCNT. The vacuum high-temperature annealing decreases the N2 adsorption amount at 77 K by more than half, supporting closing nanowindows on graphene wall of SWCNT by the vacuum annealing. Our free-standing SWCNT film is expected to promote a fundamental understanding of electrochemical energy issues by the application these films as the well-characterized electrodes. Graphical abstract: Image, graphical abstract